Modulation of redox reactivity of resazurin through host-guest complexation with Cucurbit[n]uril (n = 7, 8) - Liu, Jia; He, Su-Hang; Lambert, Hugues; Lee, Tung-Chun (Frontiers in Chemistry, 2023)
Resazurin (Alamar Blue, RZ) is a widely utilized fluorescent probe for biological sensing, whose fluorescent intensity can be modulated by changing its redox states; thereby, electrochemical reactivity of RZ is of significance when designing a sensing assay. Herein, we report novel two-way electrochemical reactivity modulation of RZ using host-guest complexation with rigid molecular containers cucurbit[n]uril (CBn, n = 7, 8). The complexation between CBn and RZ is confirmed by 1H NMR measurements and supported by computational simulation, and the binding constants are determined via UV-vis titration. Notably, the voltametric data highlights that the redox reactivity of RZ can be activated or deactivated upon encapsulation by CB8 or CB7, respectively. This two-way reactivity modulation is hypothesized to be mediated by the difference in cavity volume that favors or hinders the approach of water molecules to the encapsulated reaction center during the reduction process. Despite the similar cavity size to CB, molecular containers such as cyclodextrins (CDs) exhibit considerably weaker modulation effects. Our approach can potentially be applied to other redox processes that involve proton transfer, and open new possibilities in supramolecular electrochemistry.